Efficiency of organo-floc as a natural coagulant in the treatment of palm oil mill effluent - Ahmad Tajuddin, Husna (2015)
Palm Oil Mill Effluent (POME) contains high concentrations of chemical oxygen demand (COD), biochemical oxygen demand (BOD), and organic suspended solids (OSS) is a by product or waste of palm oil mill processing. It is compulsary to treat the POME before it can be discharged to any aqua systems. In this study, performance of Organo-floc, a natural coagulant, was evaluated as coagulation treatments for POME. The objective of the present study is to investigate the aerobic treatment of anaerobically digested POME by using a sequencing batch reactor (SBR). The SBR performance was assessed based on COD, BOD and TSS removal. The coagulation studies were carried out using a conventional jar apparatus to study the effects of various parameters which are dosage, mixing time, and speed of stirrer on the COD and TSS removal efficiencies of the anaerobic POME wastewater. Optimization on coagulation process was performed by using Response Surface Methodology-Artificial Neural Network (RSM-ANN). The central composite design (CCD) of RSM using Organo-floc as the coagulant showed that at a dosage of 5.05 mg/L and stirrer speed of 75 rpm resulted in COD removal and suspended solid removal of 34.16 % and 65.67 %, respectively. On the other hand, the ANN showed that with 5.00 mg/L of Organo-floc, at the speed of 90 rpm, the COD removal and TSS removal were 33% and 69.38%, respectively. Further treatment on POME using SBR was also investigated. SBR„s advantage is due to its simple single tank configuration and high efficiency in BOD and SS removal and cost effective treatment system for POME. Maximum COD (95 – 96 %), BOD (97 – 98 %) and TSS (98 – 99 %) removal efficiencies were achieved at optimum OLR and MLSS concentration ranges of 1.8-4.2 kg COD/m3day and 500 – 2000 mg/L, respectively. The value of the BOD data after the completion of SBR showed a reading of 150 mg/L at day-30 and 300 NTU for turbidity. The anaerobic POME wastewater without Organo-floc showed a removal range between 50 – 60 % for COD, recorded a reading of 429 mg/L for BOD and turbidity of 422 NTU at day-30. The anaerobic POME wastewater, which was treated with Organo-floc at optimal conditions prior to SBR, showed good removal efficiencies of TSS and COD when completed. Bacterial populations in the treated anaerobic POME were also studied through Denatured Gradient Gel Electrophoresis (DGGE) before and after the treatment of SBR. This was done for the purpose of improving reactor performance. The microbial community analysis recovered three major phylogenies: Firmicutes, Proteobacterium and Bacteroidetes. Strains of Rummeliibacillus suwonensis and Bacillus sp. were found during the SBR treatment. Comamonas, Bacillus subtilis and Caldanaerobius sp. were detected at the early phase of the anaerobic POME wastewater. Uncultured Bacteroidetes bacterium and Rummeliibacillus suwonensis were found alive after the completion of SBR. The effluent quality remained stable and complied with the discharge limit regulated by EQA where the value of BOD is less than 100 mg/L, no specific standard of quality for TSS and COD but the suspended solid content have to be treated and shouldn‟t reach 400 mg/L. At the same time, the sludge showed good settling properties with average SVI of 65. It is envisaged that the SBR process with added Organo-floc could complement the anaerobic treatment to produce final treated effluent which meets the discharge limit.